Prospects and roadmaps for harvesting solar thermal power in tropical Brunei Darussalam - Yahya, N.W. (Inderscience Publishers, 2021)
The need to augment Brunei Darussalamâs renewable energy sources for power generation to 10 by 2035 is necessary due to the uncertainty of oil and gas reserves. The increasing demand for electricity and the need to reduce fossil fuel consumption and greenhouse gas emissions require alternative renewable energy sources. The country should focus on the potential of solar thermal energy in generating power. As the power generated from its solar photovoltaic plant is still significantly low, this paper aims to focus on the prospects of widely used Solar Thermal Power (STP) technologies in Brunei Darussalam. Despite being commercialised in many parts of the world, the primary problem in tropical Southeast Asian regions is due to the fluctuating solar radiation, high humidity and frequent cloud cover. This study identified currently available STP technologies and further suggested approaches for large-scale power generation, and ways to minimise the issues arise from the climate conditions. Copyright Â© 2021 Inderscience Enterprises Ltd.